THE LIBERATOR NEWSPAPER AND ITS IMPACT ON THE CONDITIONS OF SLAVES (1831-1865) IN THE UNITED STATES OF AMERICA - Maha Nadhim Azeez Al-Jawdah (Proximus Journal Publishing, 2025)
The Liberator also became an avowed women's rights newspaper when the prospectus for its 1838 issue declared that as the paper's objective was "to redeem woman as well as man from a servile to an equal condition," it would support "the rights of woman to their utmost extent In January and February 1838, the Liberator published Sarah Grimké's "Letters on the Province of Woman", and later that year published them as a book, to another of Garrison and Knapp's projects Boston Female Anti-Slavery Society.[10] During the following decades, the Liberator promoted women's rights by publishing editorials, petitions, convention calls and proceedings, speeches, legislative action, and other material advocating women's suffrage, equal property rights, and women's educational and professional equality. The Liberator's printers, Isaac Knapp, James Brown Yerrinton (1800–1866) and James Manning Winchell Yerrinton (1825–1893), and Robert Folger Wallcut (1797–1884), printed many of the women's rights tracts of the 1850s. The Liberator inspired abolitionist Angelina Grimké to publicly join the abolitionist movement. She sent a letter to William Lloyd Garrison recalling her experiences as a member of an upper class, white, slaveholding family. Angelina Grimké's letter to William Lloyd Garrison was soon after published in The Liberator
Keywords: Liberator newspaper; the social conditions of the slaves